Emerging Issues in Economics and Development - Jega Ibrahim, Musa (IntechOpen, 2017)
Economics is about understanding the rational behaviour of economic agents (households, firms, industries and government) in their decisions to achieve best outcomes of their goals and aspirations. They collectively converge to achieve the utmost economic and social benefits for all in the country in terms of economic growth and development. Economic growth and development occur through efficient use of available resources to meet effective demand and social needs. The challenge that countries are facing is proper application of appropriate policy mix to optimize the opportunities of increasingly interdependent global economic landscape. For emerging economies, a multiple sector strategy that propels economic transformation is crucial. This needs to be predicated on robust macroeconomic policy framework that aligns with global production and consumption activities to drive economic growth process for achieving sustainable development.